2020
DOI: 10.1177/0143831x20969811
|View full text |Cite
|
Sign up to set email alerts
|

Public support for a union default: Predicting factors and implications for public policy

Abstract: Drawing on survey findings, in this article the authors examine levels of public support in New Zealand for a union default. The key findings are that support is high (59%), that support is principally predicted by a belief in the default’s effectiveness for improving employees’ lives, and that this belief mediates a number of other predictors, such as union membership, non-union by choice, political party, household income, gender and age. There are strong grounds for believing this would translate into actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 44 publications
4
10
0
Order By: Relevance
“…Moreover, our sample was not obviously weighted towards respondents with more positive opinions of the default, given that pro‐union groups such as younger workers and non‐voters were under‐represented. In addition, the levels of support we observed were similar to a previous NZ study of the default (Harcourt et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Moreover, our sample was not obviously weighted towards respondents with more positive opinions of the default, given that pro‐union groups such as younger workers and non‐voters were under‐represented. In addition, the levels of support we observed were similar to a previous NZ study of the default (Harcourt et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Findings indicate majority (56.1% for the control group) support a default proposal among NZ employees, consistent with what was found (59%) for a sample of the total population in an earlier NZ study (Harcourt et al, 2020, p. 1). However, levels of support and propensities to remain in membership vary across groups, mostly in ways expected.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Prior research explored how a union default would work in practice, and could be adapted to suit different employment relations regimes, including those in Britain and the US (Harcourt et al, 2021). New Zealand (NZ) studies have shown a default would attract majority support and prompt nearly two-thirds of workers to remain in unions, after being defaulted (Harcourt et al, 2020(Harcourt et al, , 2021. Notwithstanding some differences in density rates and some variations in institutional architecture, the union default is likely, we believe, to be comparably well received in other Anglophone countries, where preferences for union representation are similar to those in NZ (Freeman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%